2017
DOI: 10.1111/acer.13537
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Maternal Alcohol Problems and Parental Separation on Timing of Daughter's First Drink

Abstract: Findings highlight parental separation as an important moderator of risk to children of mothers who have a history of problem drinking, with interactive effects observed consistently across racial group. To identify underlying processes, additional research is needed with more detailed characterization of separated families where mother only has a history of alcohol problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Parental history of alcohol problems and parental separation before twins' age 18 were also modeled. Consistent with prior research (Waldron et al, 2012(Waldron et al, , 2014b(Waldron et al, , 2018, parental alcoholism was assessed from parent self-report of alcohol dependence, parental ratings of co-parent alcohol dependence symptoms, and twin ratings of each parent as a problem and excessive drinker, the latter assessed at Waves 1 and 4. Parental separation was assessed from parent and Waves 1, 3, 4, and 5 twin interviews.…”
Section: Methodsmentioning
confidence: 99%
“…Parental history of alcohol problems and parental separation before twins' age 18 were also modeled. Consistent with prior research (Waldron et al, 2012(Waldron et al, , 2014b(Waldron et al, , 2018, parental alcoholism was assessed from parent self-report of alcohol dependence, parental ratings of co-parent alcohol dependence symptoms, and twin ratings of each parent as a problem and excessive drinker, the latter assessed at Waves 1 and 4. Parental separation was assessed from parent and Waves 1, 3, 4, and 5 twin interviews.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have indicated no sex differences with regard to offspring’s risk for alcohol or substance disorders (Lieb et al, 2002; Mellentin et al, 2016). And yet, a recent study indicated that maternal alcohol problems among children of divorced parents was associated with a delayed onset of alcohol initiation among girls (Waldron et al, 2018).…”
mentioning
confidence: 99%
“…Although the reasons why parental discord predicts both initiation of regular drinking and AUD but parental divorce only predicts initiation in the AA sample are unknown, it is consistent with some prior evidence that there are racial/ethnic differences in the effects of parental divorce on children’s outcomes, which have shown that the adverse effects tend to be weaker for African American/Black children than European American/White children ( Amato & Keith, 1991 ). The racial/ethnic disparities in how adverse family experiences influence alcohol use outcomes ( Waldron et al, 2018 ) may, in part, be attributable to differences in how children react to family stressors across diverse populations ( Cichy et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%